Retrofitting of seismically deficient RC bridge pier using HSP concrete jacket and FRP rebars - Muhammad Waleed Ahmad; Muhammad Rizwan; Muhammad Fiaz Tahir (Engineering Science and Technology, an International Journal)
Bridges in high seismic zones are prone to failure due to inadequate seismic design or cumulative damage from repeated earthquakes, compromising structural integrity and functionality This study investigates the effectiveness of retrofitting seismically deficient reinforced concrete (RC) bridge piers using high-performance strength concrete (HPSC) jackets and Fiber-reinforced polymer (FRP) rebars applied at the plastic hinge zone. Two 1:4 scaled RC pier specimens with different transverse reinforcement arrangements were tested under constant axial load and quasi-static cyclic lateral loading to induce damage. The damaged piers were then retrofitted and retested to assess seismic performance improvements. Key parameters such as load-carrying capacity, hysteresis behaviour, energy dissipation, and stiffness degradation were evaluated. The retrofitted specimens showed substantial restoration of strength and stiffness and exhibited enhanced energy dissipation compared to both the original and CFRP-wrapped specimens. Additionally, a finite element model was developed in SeismoStruct (2024), showing good agreement with experimental results and validating the proposed retrofitting approach. The study concludes that the HPSC-FRP retrofit method significantly enhances the seismic resilience of damaged bridge piers and presents a viable solution for extending the service life of aging bridge infrastructure.